Synthesis, Characterization And X-Ray Studies Of Some P, As And Sb Ligands Substituted Cluster Complexes Of Ru3(Co)12 - Sirat, Siti Syaida (2013)
Triruthenium cluster substituted with Group 15 ligands were synthesized by using sodium benzophenone ketyl radical anion and thermal method. The structures of the resulting clusters were elucidated by means of elemental analysis and spectroscopic methods, such as IR, 1H, 13C and 31P NMR spectroscopy. The molecular structures of the resulting clusters were determined by X-ray diffraction. Two out of the seventeen new complexes thus identified consist of the type Ru3(CO)10(LL) [where LL = bidentate ligand] and the other complexes of the type Ru3(CO)9(LL)(L') [where LL= bidentate ligand, L'= monodentate ligand]. The disubstituted triruthenium clusters are Ru3(CO)10(dppb) and Ru3(CO)10(dpph). Both of the dppb and dpph ligands were occupying equatorial positions and the longest Ru-Ru bonds for both clusters belong to Ru-Ru bond that bridged by bidentate diphosphine ligand. The new trisubstituted triruthenium clusters are Ru3(CO)9(LL)As((C6H4)Ph)3 [LL = dppm, dpam], Ru3(CO)9(dppe)(L') [L' = As(C6H4OMe-p)3, SbPh3], Ru3(CO)9(arphos)(L') [L'= PCy3, PPh3, P(C6H4F-m)3, P(C6H4F-p)3, P(C6H4Cl-p)3, PPh(C6H4OMe-p)2, AsPh3, As(C6H4Me-m)3, As(C6H4Me-p)3], Ru3(CO)9(dppb)(L') [L' =PPh3, PPh(C6H4OMe-p)2]. All trisubstituted clusters show that the longest Ru-Ru bonds are the bonds cis to the monodentate ligand with exception for the clusters of Ru3(CO)9(arphos)PPh3, Ru3(CO)9(arphos)AsPh3 and Ru3(CO)9(dppb)PPh3,